AKTIVITAS ANTIBAKTERI EKSTRAK HERBA KROKOT (PORTULACA OLERACEA L.) TERHADAP STAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI - YUDHA KARLINA, CHRYSTIE Yudha (Universitas Negeri Surabaya, 2013)
Krokot (Portulaca oleracea L.) can be used as traditional medicine is to cure skin diseases and diarrhea. This study aimed to determine the phytochemical profile of krokot herb extract qualitatively, and to determine the effect of krokot herb extract on the growth of Staphylococcus aureus FNCC 0047 and Escherichia coli FNCC 0091. Testing the effectiveness of antibacterial calculated using test wells with bacteria S. aureus and E. coli. This study used 6 levels is 50%, 60%, 70%, 80%, 90%, 100%, positive control (ampicillin) and a negative control (distilled water). The results showed that the phytochemical profile krokot herb extract contains tannin, saponin and flavonoid. The existence of the effect of krokot herb extract against the bacteria S. aureus is characterized by the formation of zones 90% inhibition at concentrations of 2 cm, concentration of 100% of 2.2cm, beside of negative control, concentration of 50-70% not make clear zone and E. coli at a concentration of 90% of 0.6 cm, concentration of 100% of 0.9 cm, beside of negative control, concentration of 50-70% not make clear zone. Krokot herb extracts more influence on the bacteria S. aureus than E. coli bacterial wall structure is polar and easily penetrate krokot extract. Krokot herb extract concentration that is 90% and 100% effective which inhibits bacteria S. aureus. Research showed that the higher the concentration of antibacterial agent is given the greater the inhibition zone formed.